2006
DOI: 10.1136/bjsm.2005.023309
|View full text |Cite
|
Sign up to set email alerts
|

Applied physiology of tennis performance

Abstract: Competitive tennis play requires a combination of the major physiological variables; however, the specifics of these variables have yet to be determined appropriately. General strength and flexibility training have been suggested as being beneficial for performance and injury prevention, yet specific guidelines are lacking. This paper provides a review of specific studies that relate to competitive tennis, and highlights the need for tennis-specific training as opposed to generalised physical training. It iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
222
0
45

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(301 citation statements)
references
References 47 publications
1
222
0
45
Order By: Relevance
“…14,15 Therefore, adequate muscle strength and endurance are needed to perform and keep this specific movement efficiently. 16,17 Thus, the purpose of this study was to measure the KT acute effects on the handgrip maximum isometric strength (MIS) and strength endurance (SE) in healthy subjects who practice Brazilian jiu-jitsu or racquet sports.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Therefore, adequate muscle strength and endurance are needed to perform and keep this specific movement efficiently. 16,17 Thus, the purpose of this study was to measure the KT acute effects on the handgrip maximum isometric strength (MIS) and strength endurance (SE) in healthy subjects who practice Brazilian jiu-jitsu or racquet sports.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the amount of strength, speed, agility and flexibility conditioning a player is prepared to undertake is linked to the standard they play at [1]. However, in younger players, technical stroke production appears to influence rankings more than physical ability [2], and as such their training should concentrate on effective and efficient stroke mechanics, improving technique and ball placement, with less emphasis on physical conditioning. Other work has emphasised that a tactical approach to training (emphasising the role of strategy, tactics and decision making) for younger players leads to better game performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Both are argued to be suitable and practical methods for the assessment of CODS performance of tennis players due to their emphasis on both linear and lateral movement patterning, acceleration and subsequent deceleration, of which is considered highly important for tennis performance [6,7,11]. Equally, both assessments cover a total distance of 20 m, which may be pertinent to tennis as distances covered tend not to exceed 12 m [23].…”
Section: Introductionmentioning
confidence: 99%
“…Agility has been identified as key to athletic success within numerous intermittent sports [1][2][3][4][5], with tennis being a prime example [6][7][8]. Within typical tennis match play, literature reports the average point length to last less than 10 seconds, with an average of 4 changes of direction per point [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation